2005
DOI: 10.1200/jco.2005.10.081
|View full text |Cite
|
Sign up to set email alerts
|

Paroxetine Is an Effective Treatment for Hot Flashes: Results From a Prospective Randomized Clinical Trial

Abstract: Paroxetine is an effective treatment for hot flashes in women with or without a prior breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
140
0
13

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 205 publications
(162 citation statements)
references
References 24 publications
(3 reference statements)
0
140
0
13
Order By: Relevance
“…Paroxetine (Paxil; GlaxoSmithKline, Research Triangle Park, NC) is a selective serotonin reuptake inhibitor currently indicated for major depressive, obsessive compulsive, panic, social anxiety, general anxiety, and posttraumatic stress disorders (Paxil, 2012). Paroxetine and other serotonin reuptake inhibitors also have proven effective in the treatment of vasomotor symptoms (e.g., hot flashes, night sweats) in women undergoing menopausal transition (Stearns et al, 2005;Deecher and Dorries, 2007) and in patients receiving antiestrogenic cancer therapy (Fisher et al, 1998;Bordeleau et al, 2007). Paroxetine undergoes significant first-pass metabolism (Kaye et al, 1989), catalyzed largely but not exclusively by CYP2D6 (Bloomer et al, 1992;Brosen et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Paroxetine (Paxil; GlaxoSmithKline, Research Triangle Park, NC) is a selective serotonin reuptake inhibitor currently indicated for major depressive, obsessive compulsive, panic, social anxiety, general anxiety, and posttraumatic stress disorders (Paxil, 2012). Paroxetine and other serotonin reuptake inhibitors also have proven effective in the treatment of vasomotor symptoms (e.g., hot flashes, night sweats) in women undergoing menopausal transition (Stearns et al, 2005;Deecher and Dorries, 2007) and in patients receiving antiestrogenic cancer therapy (Fisher et al, 1998;Bordeleau et al, 2007). Paroxetine undergoes significant first-pass metabolism (Kaye et al, 1989), catalyzed largely but not exclusively by CYP2D6 (Bloomer et al, 1992;Brosen et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The placebo effect in this study was a 14% reduction in the 10-mg arm and a 28.5% reduction in the 20-mg arm for average hot flash scores. 9 The only statistically significant side effect between paroxetine and placebo was nausea associated with the 20-mg dose. The authors recommended that paroxetine 10 mg/day be used in practice, given the efficacy and toxicity information from this trial.…”
Section: Newer Antidepressantsmentioning
confidence: 99%
“…6,10 In addition, some of the clinical trials 8,13 largely included women who specifically did not have a history of breast cancer, demonstrating similar efficacy to that seen in patients with a history of breast cancer in other trials. 6,9,10,14 …”
Section: Hot Flashes In Survivors Of Breast Cancer Compared With Othementioning
confidence: 99%
See 2 more Smart Citations